EXPLORATION OF SCIENCE CONCEPTS IN KLAMPAR PAMEKASAN BATIK MOTIFS AS A SCIENCE LEARNING RESOURCE - Sulastri, Endang; Wulandari, Ana Yuniasti Retno; Putera, Dwi Bagus Rendy Astid; Darmawati, Vita Dwi (Universitas Tanjungpura, 2025)
Science learning fosters logical and critical thinking by integrating real word contexts, such as the Klampar Pamekasan batik motif, to enhance students understanding of biological classification. Therefore, the objective of this research is to examine the concept of science in the Pamekasan Klampar batik motif as a source for learning science. This study employs an exploratory descriptive method, which involves field observations, interviews with batik artisans and educators, and documentation analysis to comprehensively examine the classification of living organisms depicted in Klampar Pamekasan batik motifs. The data analysis technique uses descriptive analysis. The results of the exploration of Klampar Pamekasan batik motifs found several motifs in the form of living creatures such as butterflies, woodpeckers, jasmine flowers, onagadori chickens, roses, sparrows, and so on. These living things can be classified based on kingdoms, divisions, classes, orders, families, genera, and species. The Klampar Pamekasan batik motif has the potential to be a source of science learning material for the classification of living things.